Psychological health correlation of express delivery workers’ occupational stress in the information logistics environment - Lin, Meishun (Frontiers in Psychology, 2022)
With the promotion of the Internet of Things technology, more and more industries have begun to combine with the Internet of Things technology. After joining the WTO, China's market economy has continued to deepen. During this period, the e-commerce industry has developed rapidly, which has promoted the rise of the express delivery industry. While the rise of the industry provides jobs for employees, it also brings enormous pressure to employees. Due to the occupational stress of various stressors in the express delivery industry, a series of psychological problems have been caused. The purpose of this paper is to conduct a correlation study on the psychological health of express delivery workers' occupational stress in the information logistics environment. It is expected to explore the relationship between occupational stress and mental health of couriers in the context of informatization, so as to provide employees with a better working environment and reduce personal stress. This paper analyzed the inventory of express companies, and reasonably analyzed the profit composition of the inventory link. Then used a more reasonable time series seasonal coefficient method to predict the amount of incoming shipments. By acquiring psychological flexibility and stress coping strategies to reduce the severity of occupational stress of employees, it can provide a scientific basis for preventing the occurrence of related diseases. This paper used a combination of theoretical and empirical methods to discuss the psychological health and occupational stress of express delivery workers and to explore the relationship between the two. The experiment results of this paper showed that in the interpersonal sensitivity analysis, the coefficient of occupational stress is 0.052, and the degree of occupational stress is proportional to interpersonal sensitivity. The higher the occupational stress, the higher the interpersonal sensitivity index. The coefficient of occupational stress is -0.31. Occupational stress is inversely proportional to age. The older the age, the lower the interpersonal sensitivity index.